Engineering the AAV capsid to optimize vector–host-interactions. (October 2015) - Büning, Hildegard; Huber, Anke; Zhang, Liang; Meumann, Nadja; Hacker, Ulrich
Highlights: Engineering of AAV capsids optimizes efficiency and/or specificity of gene transfer. High throughput-selection of AAV libraries identifies AAV variants with novel features. Cell entry targeting strategies re-direct AAV vector tropism in vitro and in vivo . Novel generation of AAV vectors can be applied in conditions of pre-existing immunity. Tailoring AAV vector particles yields novel insight into AAV's infection biology. Abstract : Adeno-associated viral (AAV) vectors are the most widely used delivery system for in vivo gene therapy. Vectors developed from natural AAV isolates achieved clinical benefit for a number of patients suffering from monogenetic disorders. However, high vector doses were required and the presence of pre-existing neutralizing antibodies precluded a number of patients from participation. Further challenges are related to AAV's tropism that lacks cell type selectivity resulting in off-target transduction. Conversely, specific cell types representing important targets for gene therapy like stem cells or endothelial cells show low permissiveness. To overcome these limitations, elegant rational design- as well as directed evolution-based strategies were developed to optimize various steps of AAV's host interaction. These efforts resulted in next generation vectors with enhanced capabilities, that is increased efficiency of cell transduction, targeted transduction of previously non-permissive cell types, escape from antibody neutralization and off-target free in vivo delivery of vector genomes. These important achievements are expected to improve current and pave the way towards novel AAV-based applications in gene therapy and regenerative medicine.